Uncovering the neuroprotective mechanisms of curcumin on transthyretin amyloidosis - Ferreira, N (2019)
Transthyretin (TTR) amyloidoses (ATTR amyloidosis) are diseases associated with transthyretin (TTR) misfolding, aggregation and extracellular deposition in tissues as amyloid. Clinical manifestations of the disease are variable and include mainly polyneuropathy and/or cardiomyopathy. The reasons why TTR forms aggregates and amyloid are related with amino acid substitutions in the protein due to mutations, or with environmental alterations associated with aging, that make the protein more unstable and prone to aggregation. According to this model, several therapeutic approaches have been proposed for the diseases that range from stabilization of TTR, using chemical chaperones, to clearance of the aggregated protein deposited in tissues in the form of oligomers or small aggregates, by the action of disruptors or by activation of the immune system. Interestingly, different studies revealed that curcumin presents anti-amyloid properties, targeting multiple steps in the ATTR amyloidogenic cascade. The effects of curcumin on ATTR amyloidosis will be reviewed and discussed in the current work in order to contribute to knowledge of the molecular mechanisms involved in TTR amyloidosis and propose more efficient drugs for therapy.